Armageddon time - Spelman, Chris (Universal, 2022)
A deeply personal coming-of-age story about the strength of family and the generational pursuit of the American Dream
Originally released as a motion picture in 2022
Special features: Deleted scenes; Building a family cast; Growing up Gray; A grandfather's legacy
Keywords: Melodrama; Familiendrama; Families / Drama; Friendship / Drama; American Dream / Drama; Queens (New York, N.Y.) / Drama; American Dream; Families; Friendship; New York (State) / New York / Queens; DVDs; Fiction films; Coming-of-age films; Drama; Feature films; Video recordings for people with visual disabilities; Video recordings for the hearing impaired; Film; DVD-Video